Millennial Feminism at Work : Bridging Theory and Practice - Juffer, Jane, 1962- (Book collections on Project MUSE., 2021)
"This essay collection presents the voices of recently graduated college students who majored or minored in gender/sexuality studies as they reflect on the relevance of feminist studies in the work world. To what degree is it possible to practice feminism while at work, in places that aren't explicitly feminist?"--